2016
DOI: 10.1002/pnp.422
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of epilepsy

Abstract: There have been significant advances in the management of epilepsy since the appearance of bromide in 1857. In the last decade, many new drugs have been developed and general understanding of the condition has improved. Here, Pharmacist Epilepsy Practitioner, Carole Brown, considers the current choice of antiepileptic drugs (AEDs), mode of action, newer AEDS, when to start treatment, epilepsy guidelines, adverse effects of AEDs, generic substitution, therapeutic drug monitoring, driving, contraception and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Nonadherent patients with epilepsy report more difficulty in attaining seizure control than adherent patients. In addition, uncontrolled seizures result in major morbidity and mortality [26]. While SCB AEDs were shown to have greater adherence rates compared with non-SCB AEDs [27], this study evaluated the association between varying SCB adherence levels and patient-reported outcomes such as HRQoL, WPAI, HRU, and costs among patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherent patients with epilepsy report more difficulty in attaining seizure control than adherent patients. In addition, uncontrolled seizures result in major morbidity and mortality [26]. While SCB AEDs were shown to have greater adherence rates compared with non-SCB AEDs [27], this study evaluated the association between varying SCB adherence levels and patient-reported outcomes such as HRQoL, WPAI, HRU, and costs among patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a disease of abnormal CNS function, resembling, at times, a neurodegenerative disease. Epilepsy is typified by unprovoked and recurrent seizures (Brown, 2016). As inflammation plays a central role in epilepsy's pathogenesis as well as other essential mechanisms, including apoptosis, synaptic strength alterations, and unusual ion channels activity, ncRNAs also participate here with abnormal expression changes during epileptogenesis (Shao & Chen, 2017).…”
Section: The Interplay Between Ncrnas and Inflammation In Neurodegene...mentioning
confidence: 99%
“…Management of epileptic seizures requires careful therapy selection to optimise seizure control and improve a patient's quality of life (QoL) ( 9 ), balanced against significant side effects that are associated with many pharmacological treatments. The three main forms of treatment available are anti-seizure medications (ASMs), dietary modification (typically the ketogenic diet), and surgical intervention ( 4 , 5 , 7 ), with preventative ASMs remaining the mainstay of epilepsy treatment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%